A randomised, placebo-controlled phase 3 study to evaluate the efficacy and safety of ASP0113, a DNA-based CMV vaccine, in seropositive allogeneic haematopoietic cell transplant recipients. (March 2021) - Ljungman, Per; Bermudez, Arancha; Logan, Aaron C.; Kharfan-Dabaja, Mohamed A.; Chevallier, Patrice; Martino, Rodrigo; Wulf, Gerald; Selleslag, Dominik; Kakihana, Kazuhiko; Langston, Amelia; Lee, Dong-Gun; Solano, Carlos; et al.
Abstract: Background: Cytomegalovirus (CMV) is a complication of allogeneic haematopoietic cell transplantation (allo-HCT). ASP0113, a DNA-based vaccine, contains two plasmids encoding human CMV glycoprotein B and phosphoprotein 65 (pp65). We assessed ASP0113 in CMV-seropositive allo-HCT recipients. Methods: In this phase 3, randomised, placebo-controlled study, CMV-seropositive allo-HCT recipients were randomly assigned (1:1) via interactive response technology to receive five injections of 1 mL of 5 mg/mL ASP0113 or placebo. The pharmacist and designated staff were unblinded. Masked syringes maintained the blind for patients and study personnel. Efficacy and safety analyses included patients who received ≥1 dose of ASP0113/placebo. The primary efficacy endpoint was the proportion of allo-HCT recipients with composite all-cause mortality and adjudicated CMV end-organ disease (EOD) by 1 year post-transplant. ClinicalTrials.gov: NCT01877655 (not recruiting). Findings: Patients were recruited between Sept 11, 2013 and Sept 21, 2016. Overall, 501 patients received ≥1 dose of ASP0113 ( n  = 246) or placebo ( n  = 255). The proportion of patients with composite all-cause mortality and adjudicated CMV EOD by 1 year post-transplant was 35.4% ( n  = 87) with ASP0113 and 302% ( n  = 77) with placebo (odds ratio 1.27; 95% confidence interval: 0.87 to 1.85; p  = 0.205). Incidence of injection site-related treatment-emergent adverse events (TEAEs) was higher with ASP0113 than placebo. Overall incidence and severity of other TEAEs was similar between groups. T-cell response to pp65 increased over time and was greater with placebo than ASP0113 ( p  = 0.027). Interpretation: ASP0113 did not reduce overall mortality or CMV EOD by 1 year post-transplant. Safety findings were similar between groups. Funding: Astellas Pharma Global Development, Inc .